Hermeneutics of social media debates on identity politics from the perspective of communicative action - Fensi, Fabianus (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
Social media Facebook is one of the three most used social media in political communication in Indonesia. This development, on the one hand, is a good sign, where a new era has begun, where communication technology is used to win democratic competition and political sympathy, but on the other hand, the use of social media communication technology makes politics full of distortion due to the widespread phenomenon of hoaxes and hate speech.  This research was conducted with one aim, namely: to reveal the distortion of the language of debate on Facebook which is packaged in various hoaxes and hate speech related to ethnicity, religion, race and intergroup (SARA). By using the critical hermeneutics method, this research attempts to explore the context of the text, reconstruct the text, discover layers of text distortion, and analyze the text to find the author's self-emancipation and various validity claims in the text. By using the perspective of communicative action theory, this research finds the fact that political language debated on Facebook social media makes it difficult to build intersubjective consensus between writers and readers in general. Language debates that center on hate speech based on religion and ethnicity fail to build consensus to understand each other because the debate texts are dominated by mastery of language that centers on psycho-religious collective solidarity. Private languages that are centered on psycho-religious collective solidarity do not provide space for achieving intersubjective mutual understanding between text writers and text readers in general.Keywords:Communication Distortion, Hate Speech, Communicative Action, Collective Solidarity, Psycho-religious